THE USE OF EEG - SLOSARZ, Piotr (Trends in education, 2012)
Currently a rapidly growing tord of technology allows on implement new technologies into lives of people. We often don't know how some stuff works, and what secrets are hidden into them. A few year ago mobile phone was something unimaginable, not to mention about device which can read ``human thought''. Today we have such possibilities about that formerly could only dream. In the article I will show how mind can control computer program or electro-mechanic system.
Keywords: eeg; biofeedback; nowe technologie.